2011
DOI: 10.1520/jai103569
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Environment on the Crack Propagation Behavior of IN718 in the Temperature Range of the Dynamic Embrittlement

Abstract: IN718 is a standard nickel-base alloy for high temperature usage, e.g., as forged gas turbine disks. At elevated temperatures IN718 is prone to cracking by dynamic embrittlement. Dynamic embrittlement is caused by oxygen diffusion along the grain boundaries, resulting in a time-dependent intergranular decohesion. The result is a fast brittle intercrystalline crack propagation. In contrast, vacuum testing shows a drastic reduction of the crack propagation rate and a ductile, transcrystalline fracture morphology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
3
8
0
Order By: Relevance
“…The same behaviour has been perceived in other superalloys such as Waspalloy [43]. Grain boundary embrittlement has been studied in [43,44,54] where it was shown that the crack growth per cycle during unloading-reloading is much higher after a dwell time period compared to pure cyclic loading. Similar observations has been reported to occur during thermomechanical fatigue crack growth tests [42].…”
Section: Dynamic Embrittlementsupporting
confidence: 59%
See 1 more Smart Citation
“…The same behaviour has been perceived in other superalloys such as Waspalloy [43]. Grain boundary embrittlement has been studied in [43,44,54] where it was shown that the crack growth per cycle during unloading-reloading is much higher after a dwell time period compared to pure cyclic loading. Similar observations has been reported to occur during thermomechanical fatigue crack growth tests [42].…”
Section: Dynamic Embrittlementsupporting
confidence: 59%
“…It has been well established that time dependent intergranular cracking of nickel-base superalloys, under both sustained and cyclic loads, is dominated by environmental interactions with oxygen at the crack tip [53,54]. Intergranular cracking is not due to the formation of massive oxidation products along the grain boundaries.…”
Section: Dynamic Embrittlementmentioning
confidence: 99%
“…Such films, with penetration depths of around 1-10 µm ahead of the tip, have been observed in dedicated experiments in several Ni-based superalloys [67,93,94]. SAGBO as a crack propagation mechanism has been discussed and suggested as a possible crack propagation mechanism in several other papers [64,65,86,[95][96][97][98][99][100][101][102][103]. SAGBO is also supported by observations in Paper IV, Fig.…”
Section: Introductionsupporting
confidence: 70%
“…The same behaviour has been perceived in other superalloys such as Waspalloy [74]. Grain boundary embrittlement has been studied in [64,74,75] where it was shown that the crack growth per cycle during unloading-reloading is much higher after a dwell-time period compared to pure cyclic loading. Similar observations during thermomechanical fatigue crack growth tests have been reported in [73].…”
Section: Dynamic Embrittlementsupporting
confidence: 58%
See 1 more Smart Citation